2014
DOI: 10.2147/ppa.s38830
|View full text |Cite
|
Sign up to set email alerts
|

Alitretinoin for the treatment of severe chronic hand eczema

Abstract: Chronic hand eczema is a common and often debilitating condition. Alitretinoin, a 9-cis-retinoic acid and pan-retinoic acid agonist, is a new and effective systemic treatment for chronic hand eczema, which provides another treatment option. A “clear” or “almost clear” response can be achieved in up to half of patients within a 24-week course of treatment. Even higher rates of remission can be obtained with a longer duration of treatment. Alitretinoin has a favorable overall profile of adverse effects; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Of note, several studies have shown that alitretinoin is most efficacious in patients with hyperkeratotic HE King et al, 2014;. In the aforementioned study of 1,032 patients with CHE, 49% of those with hyperkeratotic CHE achieved PGA of "clear/almost clear,"…”
Section: Alitretinoinmentioning
confidence: 96%
See 2 more Smart Citations
“…Of note, several studies have shown that alitretinoin is most efficacious in patients with hyperkeratotic HE King et al, 2014;. In the aforementioned study of 1,032 patients with CHE, 49% of those with hyperkeratotic CHE achieved PGA of "clear/almost clear,"…”
Section: Alitretinoinmentioning
confidence: 96%
“…Acitretin is a second-generation retinoid that binds selectively for RAR-α, -β, -γ (King et al, 2014;Petersen & Jemec, 2009;Politiek, Christoffers, et al, 2016). As with alitretinoin, acitretin also demonstrates notable efficacy in patients with hyperkeratotic CHE.…”
Section: Acitretinmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 52 ] Vitamin A and other retinoids should not be taken along with alitretinoin because of the risk of hypervitaminosis A. [ 53 ] Systemic alitretinoin may increase the hepatotoxicity of methotrexate when given together and so must be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Other side effects include myalgia, facial flushing, dyspnea, hypertriglyceridemia, hypercalcemia and a decrease in the levels of thyroid-stimulating hormone. [ 53 ] Topical alitretinoin is associated with erythema and edema at application sites and rarely complications like vesiculation, burning, exfoliation and pareasthesias may develop. [ 7 ] Alitretinoin like other retinoids is also a teratogenic drug.…”
Section: Introductionmentioning
confidence: 99%